Apical extrusion of debris with different rotary and reciprocating single-file endodontic instrumentation systems: a systematic review and meta-analysis protocol - Muhammad Zubair Ahmad; Durre Sadaf; Marcy McCall MacBain; Ahmed Nabil Mohamed (BMJ Open)
Introduction Root canal treatment is one of the oldest dental procedures for the treatment of endodontic infection. Extrusion of debris beyond the root apex during root canal instrumentation and subsequent persistence of pain are common complications. A systematic review of the evidence on reciprocating single-file instrumentation systems and their comparison with rotary single-file systems, with apical extrusion of debris as primary outcome, will be done through this study.Methods and analysis Published ex vivo and in vitro studies with no language restriction will be included. We will search MEDLINE (Ovid), EMBASE (Ovid), Web of Science, Cochrane and Google Scholar. Strategies will be incorporated to search grey literature also. Thorough evaluation of search results, completion of data abstraction and assessment of quality will be done by two reviewers independent from each other. Assessment of included studies will be done by utilising an evidence model developed on the basis of standards of quality reported in guidelines to document ex vivo and in vitro studies regarding dental materials and pertained for extrusion of debris apically and has been already used in quality assessment of studies involving quantification of debris extrusion apically. We will calculate the standardised mean differences for apically extruded debris, with congruent 95% CIs. We will measure the statistical heterogeneity by applying the Cochrane Q test and quantify using the I2 statistic. Existence of covariates and any potential heterogeneity will be explored through prespecified subgroup and sensitivity analyses.Ethics and dissemination Approval from an ethical research committee is not required because it will be done using data that have been already published and have no concerns related to the privacy of patients. Extensive dissemination of results from this review will be done through submission to a peer-reviewed journal for publication and conferences.PROSPERO registration number CRD42019151804.